PRAGMATIC FEATURES OF ALLUSIVE UNITS IN POETIC TEXTS - Mastura Ablaxat qizi Karimova (Web of Journals Publishing, 2026)
The article highlights the specific features of the pragmatic analysis of poetic texts, focusing on the issues of communicative interaction between the author and the listener. In this context, the role of presupposition and hidden context within the poetic text is analyzed. Furthermore, based on H. P. Grice's communicative principles, the pragmatic value of poetic expression and the significance of allusive units in literary texts are revealed.
Keywords: Pragmatics, poetic text, presupposition, hidden context, communicative interaction, Grice’s maxims, allusion.